Heterozygotie slovanské mutace 657del5 NBN genu u pacientů s kolorektálním karcinomem - Seemanová, Eva; Hoch, Jirí; Seeman, Pavel (Casopis lekaru ceskych, 2011)
BACKGROUND: Nijmegen breakage syndrome (NBS) is one of the chromosomal instability syndromes due to DNA repair disorder. The syndrome is autosomal recessive determined, in homozygotes is characterized by many disorders including high predisposition to lymphoreticular malignancy in childhood and adolescence. METHODS: Laboratory findings represent low level of immunoglobulins, B and T lymphocytes, increased sensitivity to the mutagens, especially hyperradiosensitivity and increased chromosomal instability. Heterozygotes show also elevated radiosensitivity and have an increased cancer risk in adult age. There is no predilection of the malignancy. Colorectal cancer was found often among the relatives of patients with NBS. Majority of the NBS patients are of the Central and Eastern European origin and carry the common founder mutation 657del5 in the NBN gene. The formation of second malignancy both in homozygotes and heterozygotes can be prevented by excluding any radiation. The aim of study is estimation of frequency of 657del5 heterozygotes among patients with colorectal cancer. RESULTS AND CONCLUSIONS: Within a group of 161 patients with colorectal cancer 5 heterozygotes with 657del5 mutation were registered, e.g. 5-times higher incidence than expected. The elemental prevention in patients with proved positivity of Slavic mutation in NBN gene is to exclude any radiation.
Keywords: senioři; jaderné proteiny; kolorektální nádory; Nuclear Proteins; Heterozygote; Middle Aged; Colorectal Neoplasms; mužské pohlaví; mutace; Adult; Nijmegen Breakage Syndrome; Cell Cycle Proteins; Slovakia; Slovenská republika; proteiny buněčného cyklu; ženské pohlaví; Mutation; Humans; syndrom Nijmegen breakage; lidé středního věku; dospělí; Female; Aged; lidé; Male; heterozygot